Characterization and durability properties of blended cement mortar by incorporating palm oil fuel ash and bentonite clay - Hasan, Kamrul; Aizat, Alias; Fadzil, Mat Yahaya; Hasan, Mehedi; Mazumder, Roni (Springer Berlin Heidelberg, 2026)
Due to rapid urbanization and industrial development, the growing demand for concrete has increased cement production, which requires substantial raw materials, consumes significant energy, and contributes 8–10% of global carbon dioxide emissions annually. To address this issue, palm oil fuel ash (POFA), a byproduct of burning palm oil residues, and bentonite (BT), a naturally occurring clay, offer a solution to reduce reliance on cement and enhance the sustainability of the construction industry. This study investigated the effects of blended cement mortar (BCM) with varying POFA and BT inclusion levels, ranging from 0 to 20%, in 5% increments. Test on workability, water absorption, acid and sulfate resistance, and porosity were conducted, along with characterizations and microstructural analyses through X-ray fluorescence (XRF), X-ray diffraction (XRD), scanning electron microscopy (SEM), and pozzolanic activity index (PAI) to correlate the results. The environmental impact regarding emissions and energy consumption was also evaluated, together with a cost analysis. The results indicated that incorporating POFA and BT reduced the workability of the mortar. However, 20% POFA addition exhibited lower water absorption, improved resistance to acid and sulfate, reduced porosity, and lower emissions. Additionally, it required less energy and led to cost savings than control mix. Furthermore, the sample with 15% POFA and 5% BT showed satisfactory performance in comparison to the control sample. These findings demonstrate that combining POFA and BT can reduce the carbon footprint and production costs, emphasizing their role in sustainable construction.